Some Observation on the Development of Weatjering forms in the Millstone Grit of the Burbage Basin, Southern Pennines - Said, Muhammad (Journal of Himalayan Earth Sciences, 1975)
Weathering pits are formed when large quartz pebldes are removed from the surfaces of the grit blocks or tor tops. The cavities so produced are enlarged by solution, frost action and organic growth and decay. They were probably initiated in the Last Interglacial. Their development was interrupted by the onset of cold conditions in the Last Glacial. During this time cracks were produced in some of the pits due to freeze-thaw action. They are currently developing on the surface of blocks but are relict features when they occur on their sides. Honey comb weathering develops on the sloping surfaces of the grit free faces, tor plinths and blocks, where an iron deficient zone exists beneath a hard, iron-rich rock crust. The removal of quartz pebbles destroys the hard crust and exposes the inner decomposed rock, fretted with honeycomb weathering. It appears that the weathering was initiated after the detachment of blocks from the bed rock, probably rnicrogelivation played an important part in its development. The presence of an iron nodule is a pre-requisite for the development of the weathering circles. The iron-deficient zone peripheral to the iron nodule is etched out by chemical weathering and microgelivation to form circles. Their formation was contemporaneous with the Last Glaciation. As the active evolution of free faces stopped by the end ofthe Upper Dryas, circles on any free face cannot be older. than about 10,000 years. Some of the weathering circls on blocks were produced on the free faces; others have been formed subsequent to the detachment of the blocks from the freefaces.